(untitled) (Mustansiria Dental Journal, 2025)
Background: Patients with tooth misalignment are typically treated with traditional brackets during orthodontic treatment. The complexity of bracket design often hinders proper oral hygiene, resulting in an increased load of microbiota. The shape of the brackets acts as a reservoir for Candida, leading to candidosis of the oral cavity.Aims: This investigation aims to evaluate the impact of fixed orthodontic appliances on the count and distribution of salivary Candida species compared to saliva from subjects without orthodontic appliances. Methods: Eightyparticipants from the Iraqi population wearing fixed orthodontic devices comprised the study group, while 20 participants without orthodontic devices served as the control group. Salivary samples were obtained from both groups, and Candida chromogenic agar was used for cultivation. The counting and identification of different Candida species were confirmed using the Vitek 2 system to validate cultural characteristics. Results: In this study, four types of Candida species were identified: C.parapsilosis, C.albicans, C. tropicalis & C.krusei in comparison to various published researchs, this study showed no statistically significant increase in colonization by any Candida species colonization during the orthodontic treatment. However, C. tropicalis was the most frequently isolated species for both test and control groups in comparison with other species. The fixed appliances had no impact on the existence, non-attendance or scale of habitation by Candida species and there were no considerable variation in the prevalence of Candida species, based on different factors (age, gender, and saliva pH) for both test and control groups.Conclusions: The results of this study indicate that fixed orthodontic treatment had no effect on the prevalence of Candida species. This suggests that Candida accumulation may be related to an individual’s own oral flora and is influenced by oral hygiene